Implementation of Environmental Pollution and Damage Prevention Instruments in Indonesia: Issues and Challenges - Alicia, Francisca Rachel (Indonesian Journal of Environmental Law and Sustainable Development, 2024)
This paper delves into the implementation of environmental pollution and damage prevention instruments in Indonesia, highlighting the inherent issues and challenges. It scrutinizes the efficacy of existing measures in curbing environmental degradation and explores the obstacles hindering their successful execution. The findings underscore a myriad of challenges confronting the implementation process, ranging from regulatory gaps and enforcement deficiencies to institutional capacity constraints. Despite the presence of legislation aimed at safeguarding the environment, enforcement mechanisms often fall short due to inadequate resources, corruption, and lack of coordination among relevant stakeholders. Additionally, the complexity of environmental issues, coupled with rapid industrialization and urbanization, exacerbates the challenges faced in mitigating pollution and preserving natural resources. Addressing these challenges necessitates a multi-faceted approach that encompasses legislative reforms, capacity building initiatives, and enhanced collaboration between government agencies, civil society, and the private sector. Strengthening regulatory frameworks, improving monitoring and enforcement mechanisms, and promoting public awareness are crucial steps towards achieving sustainable environmental management in Indonesia. Moreover, integrating environmental considerations into broader policy agendas and fostering international cooperation are vital for addressing cross-border environmental challenges and ensuring long-term environmental sustainability. In conclusion, while Indonesia has made strides in formulating environmental policies, effective implementation remains a pressing issue. By identifying and addressing the challenges impeding the execution of pollution prevention instruments, Indonesia can bolster its environmental governance framework and pave the way for a greener and more sustainable future.